Optimizing Micro-Tiles in Micro-Structures as a Design Paradigm. (October 2019) - Antolin, Pablo; Buffa, Annalisa; Cohen, Elaine; Dannenhoffer, John F.; Elber, Gershon; Elgeti, Stefanie; Haimes, Robert; Riesenfeld, Richard
Abstract: In recent years, new methods have been developed to synthesize complex porous and micro-structured geometry in a variety of ways. In this work, we take these approaches one step further and present these methods as an efficacious design paradigm. Specifically, complex micro-structure geometry can be synthesized while optimizing certain properties such as maximal heat exchange in heat exchangers, or minimal weight under stress specifications. By being able to adjust the geometry, the topology and/or the material properties of individual tiles in the micro-structure, possibly in a gradual way, a porous object can be synthesized that is optimal with respect to the design specifications. As part of this work, we exemplify this paradigm on a variety of diverse applications. Highlights: Support for microstructures design with graded heterogeneous materials. A framework for editing microstructures, affecting individual tiles' geometry, topology, and material. Direct support for (isogeometric) analysis of microstructures.